DEVELOPING THE COORDINATION SKILLS OF PRIMARY CLASS STUDENTS - Kholmurodov, Laziz (Журнал иностранных языков и лингвистики, 2022)
This article presents a special set of exercises for the effective organization of the process of physical education of primary school students, the development of the student’s coordination abilities, depending on the age and development of physical development and the level of preparedness.